Efektivitas dan Kontribusi Pajak Reklame Dalam Meningkatkan Pendapatan Asli Daerah Kota Pontianak - Rianda Hanis; Usman Saputra (Fakultas Ekonomi dan Bisnis, Universitas Riau, 2019)
One source of funding in regional development is derived from Regional Original Revenue (PAD). The economy in Pontianak is dominated by trading in goods and services. Therefore advertisement tax is expected to be one of the components that can increase PAD in Pontianak. The reality of the Pontianak city government is still experiencing difficulties in achieving the advertisement tax collection target, so that the Pontianak city government feels it is necessary to reduce the billboard tax target by 2018. The purpose of this study is to determine (1) the effectiveness of advertisement tax collection in Pontianak in 2012 -2017 (2) The contribution of advertisement tax to PAD in Pontianak City in 2012-2017. This research uses descriptive method with quantitative approach. The data used in this study are secondary data, namely target data and advertisement tax realization and Regional Original Revenue (PAD) data obtained from Pontianak City Regional Finance Agency (BKD). Based on the results of the study, it can be concluded (1) The effectiveness of advertisement tax in Pontianak City in 2012, 2013, 2014 and 2016 is included in the very effective category, whereas in 2015 and 2017 is included in the quite effective category. The lack of effectiveness of advertisement tax in 2015 and 2017 is more due to the lack of awareness of taxpayers and the large number of non-commercial billboards. (2) The contribution of advertisement tax to the Regional Original Revenue (PAD) of Pontianak City in 2012-2017 is in the category of very under-contributing because the percentage is below 10%.